Can Australian radiographers assess screening mammograms accurately? First stage results from a four year prospective study. Issue 2 (May 2016) - Moran, S.; Warren-Forward, H.
Abstract: Introduction: Globally, the role of the radiographer is changing; some countries have developed advanced roles with specific scopes of practice. Other countries, like Australia, are in the process of this change. The aim of this research is to assess the diagnostic outcomes reported by the radiographers and compare them to those reported by current screen readers. Method: Six experienced radiographers were invited to participate in a prospective study conducted between 2010 and 2011. They were required to read 2000 mammograms each. Their results were compared with those of the radiologists. Statistical analysis of the results included overall cancer detection rates, recall rates, levels of agreement, kappa, sensitivity, specificity, accuracy, positive predictive value and negative predictive value. Results: A total of 9348 women were included in the study. The percentage of cancers detected by the radiographers ranged from 53% to 100% of the cancers detected by the radiologists. Radiologist recall rate ranged between 3.4% and 5.5% and the radiographers' range was 2.9%–9.8%. Level of agreement of the radiographers with the radiologists ranged from 90 to 96%. Conclusion: The potential for accuracy in screen reading by Australian radiographers is supported by the results of this study. Implementation of formal training is likely to result in an increase in the diagnostic accuracy of radiographers. Highlights: Radiographers prospectively read 2000 screening mammograms each. These results support potential for accuracy in screen reading by radiographers. Will advanced practice be introduced within BreastScreen Australia?.